Oral vitamin E supplements can prevent the retinopathy of abetalipoproteinaemia. Issue 3 (March 1986) - Runge, P; Muller, D P; McAllister, J; Calver, D; Lloyd, J K; Taylor, D
Abstract : Six patients with abetalipoproteinaemia are described who received large doses of oral vitamin E for between 12 and 18 years in addition to a low fat diet and supplements of the other fat soluble vitamins. The progressive retinopathy observed in untreated abetalipoproteinaemia was substantially modified and most probably prevented by this therapy. Angioid streaks were noted in one patient. Treatment with vitamin A alone did not prevent or arrest the progression of the retinal lesion.